Intravenous glucose infusion affects nitrogen retention in sheep - Mahyudin, Prapti (Indonesian Animal Sciences Society, 1998)
To investigate the effect of intravenous glucose infusion on nitrogen (N) retention, two experiments were conducted in 2 phases . The first phase (Exp 1) was to establish the time required for a stable glucose entry and the second phase (Exp 2) was designed to study the effect of different levels of glucose infusion on N retention . In Exp l, four wethers were used, each prepared with catheters in the left and right jugular veins, continuously fed luceme chaff at calculated maintenance energy level . The animals were infused continuously with saline for 2 days and thereafter with glucose solution at the rate of 21 .8 mmole/h for 6 days and again with saline on the seventh day. Glucose entry rate (GER) were measured using constant infusion of D-[6-H] glucose, on the second day of saline infusion (Day 0) and at the same period each day for the next seven days. Infusion of glucose reduced endogenous glucose entry by 30% on Day 1 and 2, by 13% on Day 3, but by Day 4 onwards endogenous glucose entry had returned to normal levels. Plasma insulin, reached its peak value on the first day of glucose infusion and subsequently declined . Plasma urea concentration declined with ensuing days of glucose infusion . It was concluded that for sheep fed maintenance energy level infused with glucose, it takes approximately 4 days for glucose metabolism to reach equilibrium. In Exp 2, four wethers were used, each prepared with catheters and fed luceme pellets at calculated maintenance energy level . The sheep were infused continuously for five days with glucose at a rate of either 0 (saline), 10, 20 and 30 mmole/h in a Latin Square design (4 infusion rate x 4 periods) . A large increase in endogenous glucose entry was found with the highest level of infusion . Glucose entry rates were 28 .8, 48.3, 54 .7 and 86.1 mmole/h for glucose infusion of 0, 10, 20 and 30 mmole/h respectively . No significant changes in both plasma glucose and urea concentration with infusion rate of glucose. N retention increased with increasing level of glucose infused (P<0.05) and was mainly due to the reduction of urinary N. This experiment suggests the important of glucose in protein deposition Â Keywords : Glucose infusion, glucose entry rate, N retention